Measuring blog influence: Recognition, activity, generation, and novelty - Hassan, Shahizan; Shiratuddin, Norshuhada; Sakdan, Mohd Fo'ad; Hashim, Nor Laily; Sajat, Mohd Samsu (IGI Global, 2012)
Netizens around the world increasingly use blogs to share thoughts and opinions, create special interest groups, collaborate, and debate on issues.However, the social influence of blogs remains largely undetermined.This paper presents the outcomes of a study which investigates how the influence of blogs can be measured quantitatively.The purpose of the study was to determine how to assess the social influence of blogs and to develop two new tools for measuring blog influence: the Blog Influence Index (BII) and Blog Influence Analyzer (BIA).These tools were applied to identify top influential blogs in the blogosphere community of Malaysia.The results indicate that the top 10 most influential blogs in Malaysia fall under the categories of politics, entertainment, sports, lifestyle, and technology.